Training on Beach Tourism Through Social Media: Citizen Journalism News Content Production in Sawarna - Antonius Setyadi; Achmad Jamil; Lucky Nugroho (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
In the information age like today, we are presented with a lot of news, both from within the country and abroad. Now, in the information age, we get news not only from the media but also through the internet. In producing news broadcasts, it is necessary to first understand what news value is. Because the viewers should not be treated to news that is not at all useful as information. This is necessary to find out what information they need. The bottom line: we must first examine and examine what events or incidents should be made as news. Indonesia is a maritime country, which means it has many islands. This causes Indonesia to be rich in natural resources. One of the interesting destinations to be covered as news material is Sawarna. From the results of the training, participants need ongoing training to create positive news content by promoting interesting tourism in Sawarna on social media through citizen journalism, but many participants are satisfied with what the presenters are presenting and get a basic overview of the practice process of producing news content in Sawarna on social media. through citizen journalism. In addition to doing role playing, the presenters provide games or games by asking questions about the material that has been presented. The implementation of this service aims to determine the impact of promotional strategies in increasing tourist visits and to find out the most effective promotional strategies in increasing tourist visits to tourism. This research uses two methods, namely the Troubleshooting Framework method and the Activity Method. Data collection was carried out through interviews, direct observation of documentation, and workshop activities, which were attended by 18 participants. The results of this research show that 1. Overall, the participants stated that this workshop was interesting; many new things were obtained and learned during the activity. The training material is very useful in